Formulation a Strategy to Increase the Competitiveness of SMEs: a Case Study on the Industry of Batik Bojonegoro - Hidayat, Taufiq; Pristian Fitri Astuti, Rika; Mujahidin, Ali (KnE Social Sciences, 2022)
Batik has quite a stable market trend, both in national and international markets. Almost every region in Indonesia has a specific and unique batik product. On one side, this condition enriches national batik variation so that consumers have many choices. On the other side, it triggers competitiveness, particularly in the national batik market. Therefore, SMEs working with batik must have competitiveness in encountering competitors. This research aimed to formulate a strategy that improves the competitive advantage of the Batik Bojonegoro Industry. The researcher employed a qualitative approach. Managers and employees of Batik Bojonegoro Industry were the research subjects. The data were collected through interviews, documentation, and observation which were then analyzed by Internal Factor Evaluation (IFE) Matrix, External factor Evaluation (EFE) Matrix, Internal-External (I-E) Matrix, and Quantitative Strategic Planning Matrix (QSPM). The research result showed that the Product Development Strategy is the best strategy to improve the competitiveness of the Batik Bojonegoro Industry. This strategy has the highest Sum Total Attractiveness Scores (STAS) value on the QSPM matrix by 5.81. Product Development Strategy is the most appropriate strategy for Batik Bojonegoro SMEs to confront the power of competition and strengthen the competitiveness of businesses. Keywords: Business strategy, competitiveness, SME, Batik Bojonegoro.